Check if the Full-back J(5,-3) and centre-back I(-4,6) are equidistant from forward C(0,1) and if C is the mid-point of IJ.
Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class
CBSE Class 10 Sample Paper for 2024 Boards - Maths Standard
Question 2
Question 3
Question 4 Important
Question 5
Question 6 Important
Question 7
Question 8 Important
Question 9
Question 10
Question 11
Question 12 Important
Question 13
Question 14
Question 15
Question 16
Question 17 Important
Question 18
Question 19 [Assertion Reasoning]
Question 20 [Assertion Reasoning]
Question 21 Important
Question 22
Question 23
Question 24 (Choice 1) Important
Question 24 (Choice 2)
Question 25 (Choice 1)
Question 25 (Choice 2)
Question 26
Question 27 Important
Question 28 (Choice 1) Important
Question 28 (Choice 2) Important
Question 29 (Choice 1) Important
Question 29 (Choice 2) Important
Question 30
Question 31
Question 32 (Choice 1) Important
Question 32 (Choice 2) Important
Question 33 (a) Important
Question 33 (b) Important
Question 34 (Choice 1)
Question 34 (Choice 2) Important
Question 35 Important
Question 36 (i) [Case based]
Question 36 (ii) (Choice 1)
Question 36 (ii) (Choice 2) Important
Question 36 (iii)
Question 37 (i) [Case based]
Question 37 (ii) (Choice 1)
Question 37 (ii) (Choice 2) You are here
Question 37 (iii)
Question 38 (i) [Case based]
Question 38 (ii) (Choice 1)
Question 38 (ii) (Choice 2)
Question 38 (iii) Important
CBSE Class 10 Sample Paper for 2024 Boards - Maths Standard
Last updated at Aug. 4, 2023 by Teachoo
Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class
We need to check if C is equidistant from J and I And C is mid-point of IJ Doing this one by one Check if C (0, 1) is equidistant from I (−4, 6) and J (5, −3) To prove if point C is equidistant from I & J We need to prove CI = CJ Since CI = CJ ∴ C is equidistant from I and J Finding CI CI = √(( −𝟒 −𝟎)𝟐+(𝟔−𝟏)𝟐) = √((−4)2+(5)2) = √(16+25 ) = √𝟒𝟏 Finding CJ CJ = √(( 𝟓 −𝟎)𝟐+(−𝟑−𝟏)𝟐) = √((5)2+(−4)2) = √(25+16 ) = √𝟒𝟏 Check if C (0, 1) is midpoint of I (−4, 6) and J (5, −3) If C is mid-point of IJ Coordinates of C = ((𝑥1 + 𝑥2)/2,(𝑦1 +𝑦2)/2) (0, 1) = ((−𝟒 + 𝟓)/𝟐,(𝟔 + (−𝟑))/𝟐) (0, 1) = (1/2,3/2) Since LHS ≠ RHS ∴ C is NOT the mid-point of IJ Now, AC = BC √(𝒂𝟐−𝟒𝒂+𝟖) = √(𝒂𝟐−𝟏𝟒𝒂+𝟔𝟓) Squaring both sides (√(𝑎2−4𝑎+8) " )2 = (" √(𝑎2−14𝑎+65))^2 𝒂𝟐−𝟒𝒂+𝟖 = 𝒂𝟐−𝟏𝟒𝒂+𝟔𝟓 −4a + 8 = −14a + 65 −4a + 14a = 65 − 8 10a = 57 a = 57/10 a = 5.7